The Arabic Poetry Of Al-Tafi’ila: Between The Terminology And the Rhythmic Determinants - Alomari, Salameh Mohammad Rida (Ijaz Arabi Journal of Arabic Learning, 2024)
This study aims to clarify the rhythmic values of Arabic poetry's ancient and modern meters as an essential tool in Arabic language teaching/learning. It seeks to enable the students to compare and contrast the Arabic rhythm in terms of 'Tafi'ila.' It is based on pursuing the facts of the connection and the separation between the deliberative prosodic studies' description of the nature of the rhythm that governs what is called the term 'Al-Tafi'ila poetry.' In addition, the path of verifying this rhythm in modern Arabic poetry is done through the systematic investment in Al-Khalil's theory to examine the rhythmic basis of Al-Tafi'ila poetry. It is found that this examination of the theory of traditional prosody allows us to remove the ambiguity about the claims of the radical modernization brought about by the "Al-Tafi'ila" system in the contemporary Arabic poem. It will also establish a comprehensive conception of the reliability of the term "Al-Tafi'ila poetry" in representing the rhythmic nature of the poems that belong to it.